Total internal reflection-based single-vesicle in situ quantitative and stoichiometric analysis of tumor-derived exosomal microRNAs for diagnosis and treatment monitoring - He, Dinggeng; Wang, Huizhen; Ho, See-Lok; Chan, Hei-Nga; Hai, Luo; He, Xiaoxiao; Wang, Kemin; Li, Hung-Wing (Theranostics, 2019)
: Exosomes (EXs) have been increasingly recognized as natural nanoscale vehicles for microRNA (miRNA)-based cell-cell communication and an ideal source of miRNA biomarkers in bodily fluids. Current methods allow bulk analysis of the miRNA contents of EXs, but these approaches are not suitable for the in situ stoichiometry of exosomal miRNAs and fail to reveal phenotypic heterogeneity at the single-vesicle level. This study aimed to develop a single vesicle-based, mild, precise, but versatile method for the in situ quantitative and stoichiometric analysis of exosomal miRNAs. : A total internal reflection fluorescence (TIRF)-based single-vesicle imaging assay was developed for direct visualization and quantification of the single-vesicles of EXs and their miRNA contents in serum microsamples. The assay uses co-delivery of inactive split DNAzymes and fluorescence-quenched substrates into nanosized EXs treated with streptolysin O to produce a target miRNA-activated catalytic cleavage reaction that amplifies the readout of fluorescence signal. We perform the in situ quantitative and stoichiometric analysis of serum exosomal hsa-miRNA-21 (miR-21), a common cancer biomarker, by using the developed TIRF imaging assay. : The TIRF imaging assay for serum exosomal miR-21 can distinguish cancer patients from healthy subjects with better performance than conventional real-time polymerase chain reaction (PCR) assay. The exosomal miR-21 level in serum is also informative for monitoring tumor progression and responses to treatment. Moreover, the TIRF assays can readily determine the precise stoichiometry of target exosomal miRNA contents in situ by delivering molecular beacon (MB) probes into EXs. : The created TIRF imaging platform shows high applicability to serve as a universal and useful tool for the single-vesicle in situ quantitative and stoichiometric analysis of other disease-associated exosomal miRNAs markers and provide valuable insight into the physiological relevance of EX-mediated miRNA communication.